Diseño de un sistema de parqueo vertical tipo carrusel, para la Fundación Universidad de América sede Campus los Cerros (2020)
This project is focused on the design of a vertical rotary parking lot for the optimization of spaces for parking of vehicles in the student parking lot of the University of America Foundation.Based on the above, the project was documented with district and structural standards; design parameters and solution alternatives were also determined which were selected under the QFD method in order to find the most optimal alternative. The preliminary design was then carried out where the pertinent calculations were made for the adequate design of the carousel-type vertical parking system. Maintenance manuals, assembly, manufacturing drawings, cost analysis, an approach to the operational part of the basic instrumentation system and an approach to the environmental impact that the implementation of this type of systems would generate in the area are carried out.